Borders and Nominal Exchange Rates in Risk-Sharing. Issue 3 (28th March 2019) - Devereux, Michael B; Hnatkovska, Viktoria V
Abstract: Models of risk-sharing predict that relative consumption growth rates are positively related to changes in real exchange rates. We investigate this hypothesis using a new multicountry and multiregional data set. Within countries, we find evidence for risk-sharing: episodes of high relative regional consumption growth are associated with regional real exchange rate depreciation. Across countries, however, the association is reversed: relative consumption and real exchange rates are negatively correlated. We define this reversal as a "border" effect. We find the border effect and show that it accounts for over half of the deviations from full risk-sharing. Since cross–border real exchange rates involve different currencies, it is natural to ask how much of the border effect is accounted for by movements in exchange rates. Our measures indicate that a large part of the border effect comes from nominal exchange rate fluctuations. We develop a simple open economy model that is consistent with the importance of nominal exchange rate variability in accounting for deviations from cross–country risk-sharing.